2011
DOI: 10.1097/opx.0b013e3181fc329f
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor as a Biomarker in Primary Open-Angle Glaucoma

Abstract: We conclude that BDNF in the serum might be a useful biochemical marker for early detection of POAG. We also propose that this might be a reliable, time efficient, and cost-effective method for diagnosis, screening, and assessing the progression of POAG. However, more studies and trials are needed to investigate these factors in greater detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 41 publications
1
40
0
2
Order By: Relevance
“…[26][27][28] In the only study investigating serum BDNF levels in AMD, serum BDNF levels were found to be significantly higher in AMD patients compared to controls. 29 The authors concluded that BDNF release from the CNS may be increased in response to degenerative process in the retina and confounding factors such as stress and exercise might affect their outcome.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] In the only study investigating serum BDNF levels in AMD, serum BDNF levels were found to be significantly higher in AMD patients compared to controls. 29 The authors concluded that BDNF release from the CNS may be increased in response to degenerative process in the retina and confounding factors such as stress and exercise might affect their outcome.…”
Section: Discussionmentioning
confidence: 99%
“…BDNF is transported to the retinal ganglion cell bodies through a retrograde axonal transportation system and the synaptic connections within (45) . BDNF in the tears of normal tension glaucoma patients is signifi cantly less than normal, and this may be a potential diagnostic biomarker for early detection of normal tension glaucoma.…”
Section: Bdnfmentioning
confidence: 99%
“…BDNF crosses the blood-brain barrier and as a result, the level of this factor in the blood can relatively refl ect its concentration in the brain. BDNF levels in serum were determined in POAG patients and controls by ELISA (45) . The authors concluded that BDNF in the serum might be a useful biochemical marker for early detection of POAG.…”
Section: Bdnfmentioning
confidence: 99%
“…BDNF has been found significantly decreased in the tears of normal tension glaucoma patients and open angle glaucoma patients in comparison to controls (Ghaffariyeh et al, 2011).…”
Section: Molecular Biomarkers In Glaucomamentioning
confidence: 98%